Kewenangan Mahkamah Agung dalam Publikasi Pada Putusan Perkara Privat - Ningrum, Vernita Kusuma; Hufron, Hufron (Universitas Wijaya Putra, 2024)
This study examines the Supreme Court's authority to publish rulings on private cases and its impact on individuals' privacy rights. This authority, framed by transparency and data protection principles, is grounded in the right to public information per the Indonesian Constitution and Law No. 14 of 2008. However, publishing decisions in sensitive cases, such as divorce and domestic violence, risks violating individual privacy. This research addresses the urgent need to balance transparency and privacy by analyzing the legal basis and limitations on the Court’s authority. Through normative legal methods and legislative analysis, this study reviews key guidelines, including Supreme Court Decision No. 2-144/KMA/SK/VIII/2022, to recommend privacy protections for sensitive information in judicial rulings. Findings indicate that, despite a general obligation to disclose court decisions, exceptions must be made for sensitive data to safeguard privacy, contributing to a nuanced approach to judicial transparency.